The Study of the Application of Hybrid Propulsion System on OPV with Controllable Pitch Propellers - Eddy Setyo Koenhardono; . Amiadji; Rahmat Kristomi (International Journal of Marine Engineering Innovation and Research, 2017)
As a patrol ship, the offshore patrol vessel (OPV) 80 m has an operational profile consisting several conditions: loitering (10 knots), patrol (18 knots), and interception (22 knots). Applying diesel mechanical propulsion system, load factor of each OPV 80 m’s main engine during loitering (10 knots) and patrol (18 knots) conditions in sequence is just about 7% and 49.54%. The load factor permitted by the engine maker ranges between (60% ~ 90%) MCR, however. By applying hybrid propulsion system, the load factor of the OPV 80 m’s shaft motor during loitering condition is 87.26% while the load factor of its main engine during patrol and interception conditions becomes 62.10% and 89.949%.In terms of economical aspects, for 30 years of operation period of OPV 80 m, total of present values of hybrid application is significantly much lower than of diesel mechanical application, with the difference between them is IDR 579.205.295.632,-.